Investigation and analysis the vibration of handles of chainsaw without cutting - M Feyzi (Ferdowsi University of Mashhad, 2016)
Introduction: Nowadays most of the agricultural and industrial tasks are performed using different machines and almost any people are exposed to the vibration of these machines. Just as sound can be either music to the ear or irritating noise, human vibrations can either be pleasant or unpleasant. Whole-body vibration and hand-arm vibration are two main types of unpleasant vibration. The hand-arm transmitted vibration can cause complex vascular, neurological and musculoskeletal disorder, collectively named as hand-arm vibration syndrome. The chainsaw is a portable machine, powered by a two-stroke engine. This machine is used by tree surgeons to fell trees, remove branches, and other activities such as prune trees. The chainsaw exposes own operators to high level of hand-arm vibration which can lead to problems such as vibration white finger syndrome and Raynaud's phenomenon. White finger syndrome affects the nerves, blood vessels, muscles, and joints of the hand, wrist and arm. It is clear that before trying to control the vibrations, the level of vibrations should be identified. Therefore, an investigation on the vibration level of this machine is crucial. Materials and Methods: The Stihl-MS230 chainsaw was selected in this study. The size of this type of chainsaw is middle and it is equipped with anti-vibration system. According to the ISO-7505 standard, vibration must be measured at three speed level of engine. First at idling speed, second at nominal speed and third at 133% of the nominal speed or maximum speed of engine whichever is less (Racing). So 2800, 10000, and 13300 RPM Engine speed were selected. One of the employed accessories was ARMA ETI-TACHO tachometer which had been fabricated in Taiwan. The vibrations were measured and analyzed using the portable data acquisition system (Easy Viber). During the measurements, data acquisition system was powered by internal batteries. The vibrations were sensed by the piezoelectric accelerometer (VMI-192). The accelerometer mounted on an adapter inserted between the handle and accelerometer. The experiments were conducted in split plot completely randomized design. Ninety tests in two handles, three speeds of engine, three perpendicular axes and five repeats were conducted. The vibration acceleration at various conditions was measured and the root mean square of vibration acceleration was calculated based on acceleration-time spectrum. To investigate the characteristics of vibration in different speeds, the vibration spectrums in time domain were converted to spectrums in frequency domain. The frequency weighted RMS acceleration at 1/3rd octave bands from 6.3Hz to 1250Hz and the vibration total value was calculated from frequency spectrum. To analyze the obtained data, SAS software was used. Furthermore, the Duncan's multiple range tests were used to compare the RMS values. Results and Discussion: Main source of vibration of chainsaw was single cylinder engine. The acceleration spectra of employed chainsaw had peaks in frequencies in accordance with the speed of engine. These peaks in 2800 rpm, 10000 rpm and 13300 rpm speeds of engine occurred in 46.5Hz, 166.5Hz and 221.5Hz, respectively. To achieve a safe design for handle of portable tools, identifying the frequency which leads to the maximum value of vibration acceleration is very useful. To avoid the resonance phenomenon, the natural frequency of handle must be far from dominant frequency of engine. The results of ANOVA showed that the RMS acceleration in different axes and different speeds were significant at 1% level. The maximum value of vibration acceleration, at idling engine speed, occurred in the lateral axis. In addition, the mentioned variable was maximized in normal and axial axes at nominal and racing speeds, respectively. The total value of vibration was increased when the speed of engine moving away from nominal speed. This increase in rear handle is very larger than front handle. The total value of vibration was maximized under rear handle and idling engine speed conditions. So the exposure to white finger disorder in right hand of operator is more probable. Total daily duration of exposure was assumed to be equal to 2h. According to the international standard (ISO 5349), 10% of the users can expect developing the symptoms of white finger syndrome less than seven years. Conclusions: In chainsaw, strokes caused by combustion are the main source of vibration. On the front handle, the maximum value of vibration acceleration, at 2800, 10000 and 13300 RPM engine speed, occurred in the lateral, normal and axial axes respectively. The vibration acceleration value was maximized under rear handle and racing engine speed conditions caused by large value of vibration acceleration at 400Hz center of 1/3rd octave bands. The total value of vibration in idling and racing engine speeds, on rear handle are more than front handle significantly but in nominal engine speed, on rear handle is less than front handle.